Electron-Beam Welding of Laser Powder-Bed-Fused Inconel 718 (International Journal of Engineering Materials and Manufacture, 2021)
This study explores the application of Electron-Beam Welding (EBW) for joining Laser Powder-Bed-Fused Inconel 718 (L-PBF IN718) superalloy. Three different levels of electron beam speed and beam current were explored to give nine different electron beam heat inputs for experimentation. To define the weld characteristics microhardness, tensile, and fractography analysis using scanning electron microscopy, optical microscopy, and energy dispersive spectroscopy were conducted. Typical nail-shaped weld geometry was observed with penetration depth proportional to heat input. Most welded samples exceeded the yield strength (600MPa) and tensile strength (920MPa) requirements from the ASTM F3055 specifications for additively manufactured IN718, however, the specimens did not meet the ductility requirements (27%). Brittleness of the weld was attributed to the presence of brittle secondary phases in the weld matrix, and unfused metal powder of adjacent L-PBF layers. Post-processing heat treatments were recommended to improve the weld quality while improving the ductility of EBW joints.